KEPEMIMPINAN KEPALA MADRASAH DALAM UPAYA MENINGKATKAN KINERJA GURU DI MA AL FALAH GUNUNG KASIH KECAMATAN PUGUNG KABUPATEN TANGGAMUS TAHUN AKADEMIK 2021/2022 - Deden Purwa; Feriansyah; Yuli Habibatul Imamah (UNISAN JURNAL, 2022)
This research is specifically to find out how the principal’s leadership in improving teacher performance at MA Al Falah Gunung Kasih, the factors that can influence and factors that can improve teacher performance, are expected. By knowing all that, some suggestions can be given that can be taken into consideration for school principals, especially in improving the performance of teachers in their schools. This study uses a qualitative approach, while the data collection uses participant observation techniques, interviews, and documentation. For data analysis using three flow of activities, namely data reduction, data presentation and drawing conclusions. From the results of the study, it was stated that the principal’s leadership was considered good, but had not had a positive impact on improving teacher performance at Al Falah Gunung Kasih MA. While the performance of teachers at MA Al Falah Gunung Kasih is considered good, but has not run optimally as expected, this is due to the lack of teacher ability in preparing learning tools, especially Learning Implementation Plans, inadequate school facilities and infrastructure, and also the difficulties of teachers in creating educational interactions between students and teachers, as well as the difficulty of creating a conducive classroom. However, at the level of evaluation/assessment of learning outcomes, the average teacher has implemented it well and added remedial and enrichment programs. Keywords: Islamic Education Management and Santri Discipline